Elucidation of the cellulose nanocrystal-sugar beet pectin interactions for emulsification enhancement. (February 2023) - Lin, Jiawei; Tang, Zhong-Sheng; Chandrapala, Jayani; Brennan, Charles Stephen; Han, Zhong; Zeng, Xin-An
Abstract: Commercial emulsions are usually stabilized by multi-component formulations, such as particle and biopolymer, rather than single emulsifiers. However, their interactions and contributions to emulsification are complicated and lack elucidations. This work investigates the interaction between cellulose nanocrystal (CNC) and sugar beet pectin (SBP) and their performance in emulsion stabilization. The irreversible adsorption of SBP onto the CNC surface was verified by Quartz Crystal Microbalance with Dissipation (QCM-D) and atomic force microscopy. The molecular structure-based adsorption mechanism was elucidated by the enzymatic hydrolysis technique, revealing that the neutral sugar side chains (rich in protein and ferulic acid) were the main adsorbable components of SBP, which was predominately driven by hydrophobic interactions. At the CNC: SBP ratio of 3:1, the mixture of SBP-coated CNC and free SBP showed synergistic emulsification performance. The incorporation of CNC significantly improved the anchoring rate of SBP at the oil-water interface during emulsification to produce smaller emulsion droplets. The hybrid coverage of SBP-coated CNC and free SBP endowed the droplets with more robust repulsion to maintain long-term stability. These findings provide a feasible and convenient way for modulating the emulsifying properties of CNC by changing the compositional formulation. Graphical abstract: Image 1 Highlights: Cellulose nanocrystal (CNC) adsorbed with sugar beet pectin (SBP) in solution. The adsorbable fractions of SBP were neutral sugar, protein, and ferulic acid. The interaction was predominated by hydrophobic interaction. CNC and SBP showed a synergistic stabilization effect to stabilized emulsions.